A research on systematizing a common LoD system over multiple 3D description systems for urban and built environment - TOYODA, Keisuke; MIYATAKE, Sotaro (SEISAN KENKYU, 2023)
While it is foreseen that various types of autonomous agents will coexist with us on a daily basis, it is difficult to say that the development and systematization of a digital twin environment that these agents can rely on in a general-purpose manner has progressed sufficiently at present. In this study, based on the current situation where different spatial description specifications are used separately in different industrial domains, we investigate the current status and summarize the issues and possibilities for the future with a view to systematizing and implementing LoD (Level of Detail / Development) across multiple spatial description specifications. Then, we presented a frame that enables the coordination and conversion of LoDs between different specifications.